Disposal Management Practices of Unserviceable Electronic Resources - Joselito Tangaran; Donald M. Patimo; Rodolfo F. Dollado (Sriwijaya Journal of Environment, 2021)
Establishment and household-generated electronic wastes are becoming a significant problem. Literatures showed that the volume of electronic wastes generated worldwide is increasing thus becoming a threat to the environment and human health. In the local setting, Calbayog City is experiencing the same dilemma on electronic waste. This problem prompted the researchers to conduct this study. This study aimed to assess the disposal management practices of unserviceable electronic resources as observed in Calbayog city and identify the problems encountered in the disposal management of electronic wastes resources. The questionnaire was used as the primary research instrument to gather data. The respondents of the study were households and establishments in Calbayog city. In addition to the questionnaire, the researchers conducted an interview, inventory and actual site visit to the landfill area. The result showed that among the identified disposal management practices, the repair to extend the life of electronic resources was commonly observed by the respondents. On problems, lack of disposal facilities for e-wastes was the most felt problem by the respondents. The researchers concluded that an electronic waste management facility should be provided by the local government so that the establishments and households in Calbayog City can sustain the positive practices in waste disposal and eventually minimize the problems on electronic waste disposal.